Prediction of health information-seeking behavior components based on health anxiety among users of public libraries - Nasrin Musarezaie; Rahele Samouei; Leila Shahrzadi; Hasan Ashrafi-Rizi (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: This study aimed to predict health information-seeking behavior (HISB) components based on health anxiety among users of public libraries. MATERIALS AND METHODS: This research was a descriptive-correlational study. The statistical population consisted of users of public libraries. Data collection tools included the HISB questionnaire and the Short Form of Health Anxiety Inventory (SHAI). RESULTS: The results indicated that health anxiety was a significant predictor of the components of HISB. The illness likelihood had a direct relationship with the components of the need for health information and the purposefulness of health information seeking, and it was inversely related to barriers to obtaining health information. In addition, the preoccupation with illness was directly related to the components of the need for health information, the diversity of health information sources, the time of referring to health information sources, the purposefulness of health information seeking, and evaluation of reasons for referring to the library. CONCLUSION: Among the components of health anxiety, preoccupation to the disease has the highest role in the emergence of users' information-seeking behavior.